Changes in asthma self-management knowledge in inner city adolescents following developmentally sensitive self-management training. Issue 4 (April 2018) - Mammen, Jennifer R.; Rhee, Hyekyun; Atis, Shannska; Grape, Annette
Highlights: Adolescents demonstrated poor asthma self-management knowledge prior to training. Adolescents' ability to recognize uncontrolled or life-threatening asthma at baseline was low. Developmentally sensitive training significantly improved self-management knowledge. Substantial improvements were found across multiple key areas of asthma knowledge. Adolescents were able to successfully apply knowledge to common asthma management situations. Abstract: Objective: To evaluate efficacy of a developmentally sensitive curriculum for improving asthma self-management knowledge, attitude, and self-efficacy in adolescents. Methods: Fourty-two inner-city adolescents (ages 16–20) participated in a 12 hour asthma self-management training program. Self-management knowledge, attitude toward asthma, and asthma-related self-efficacy were measured using short-answer tests before and after training. T-Tests were used to evaluate impact and effect sizes were calculated. Results: Mean pretest knowledge was 21.37/46 points; mean posttest was 36.33/46 points. Change from pre- to posttest was highly significant (t = 10.34; p < 0.0001), with a large effect size (d = 1.68). Females improved more than males (18.66 ± 8.58 vs. 12.29 ± 8.13, p = 0.039). Greatest effects were seen in awareness of long-term consequences of uncontrolled asthma (d = 2.04), ability to recognize symptoms of life-threatening asthma (d = 1.61), correctly monitor symptoms (d = 1.49), and tell if asthma was uncontrolled (d = 1.39). Asthma self-efficacy also improved significantly (p = 0.017), particularly confidence in ability to correctly manage asthma, however improvements in attitude did not achieve statistical significance. Conclusion: Developmentally appropriate training is effective in increasing critical self-management knowledge and self-efficacy in inner city adolescents, particularly females. Practice implications: Providers should screen carefully for symptoms and educate using developmentally appropriate training materials on ways to correctly monitor and manage symptom.